IDENTIFIKASI FAKTOR-FAKTOR KESULITAN BELAJAR PESERTA DIDIK PADA MASA PANDEMI COVID-19 MATA PELAJARAN EKONOMI KELAS XI SMAN 11 PONTIANAK - Yulianti, Annisa; Okianna, Okianna; Budiman, Jumardi (Universitas Tanjungpura, 2022)
AbstractLearning is one of the obstacles experienced or experienced by a student in thelearning process to be able to achieve good learning outcomes. As for the causesexperienced by students who become believers into 2, namely internal factors(intellectual, etc.) and external (social environment, etc.). This study aims to beable to identify the factors of student learning difficulties during the covid-19pandemic in economics class XI SMAN 11 PONTIANAK. The informants in thisstudy were to find 20 students of class XI as many as 20 people. This type ofresearch is a qualitative description that identifies the factors of studentdifficulties during the covid-19 pandemic. Data collection techniques used in thisstudy added 3 namely observation, interviews and documentation. The results ofthe research and discussion showed that the factors of learning difficulties forstudents during the Covid-19 pandemic in class XI economic subjects wereinternal factors such as lack of interest in learning and understanding of studentsduring learning. While external factors such as media and networks and theallocation of learning time are bold.Keywords : Learning, Covid-19 Pandemic, Factors, Learning Difficulties.